Privatization and changes in the wage structure: evidence from firm personnel records - Blaise Melly; Patrick A. Puhani (Institute for the Study of Labor (IZA), 2008)
We investigate the wage effects of privatization using person-level firm-based panel datasets from one privatized and one nonprivatized public sector firm in the same country for the years immediately before and after privatization. Thus, we can analyze the before-after effects of privatization while controlling for individual and time fixed effects and allowing for firm-specific trends. Because the change in wage regime coincides with substantial losses in the market share of the privatized but not the nonprivatized firm, the situation approximates a natural experiment in switching workers from the public to the private sector. We find significant changes in the wage structure of the privatized but not the nonprivatized firm. Specifically, wage and wage growth distributions widened significantly after privatization. Conditioning on worker characteristics, we find that younger employees and those with shorter tenure gained from privatization, while high-skilled workers gained relative to medium-skilled workers. Surprisingly, low-skilled workers also gained, although seemingly in the form of temporary compensation intended to increase acceptance of privatization.
urn:nbn:de:101:1-20081126155
Keywords: J31; 330; Privatization; liberalization; competition; labor markets; wage distributions; Lohnstruktur; Öffentliches Unternehmen; Privatisierung; Wirkungsanalyse; Deutschland